DETEKSI FORMALIN PADA TAHU MENGGUNAKAN EKSTRAK ANTOSIANIN DARI KULIT NAGA (Hylocereus polyrhizus) - Novianty Novianty (Masker Medika, 2023)
Introduction: Tofu is one of food that is much liked by the public, because it has a relatively high nutritional content and has a low price, however, tofu is also a food that is often given formalin by unscrupulous producers with the aim of extending the shelf life and maintaining the quality of tofu so that it remains visible good. Objective: to determine the effectiveness of dragon fruit peel extract in detecting formaldehyde content in tofu. Method: This research is an experimental research. The sampling technique used is purposive sampling. The sample used is white tofu. There were 3 treatments with 3 repetitions consisting of P1 (5%), P2 (10%), and P3 (15%). Results: The results showed that P3 (15% anthocyanin extract of dragon fruit skin) was the most effective in detecting formaldehyde in white tofu. There were 7 positive samples containing formalin. Conclusion: Anthocyanin extract from dragon fruit peel with 15% concentartion was effective as a formaldehyde detector in food.